Hybrid Data Fusion and Tracking for Positioning with GNSS and 3GPP-LTE. (24th June 2010) - Mensing, Christian; Sand, Stephan; Dammann, Armin
Abstract : Global navigation satellite systems (GNSSs) can provide reliable positioning information under optimum conditions, where at least four satellites can be accessed with sufficient quality. In critical situations, for example, urban canyons or indoor, due to blocking of satellites by buildings and severe multipath effects, the GNSS performance can be decreased substantially. To overcome this limitation, we propose to exploit additionally information from communications systems for positioning purposes, for example, by using time difference of arrival (TDOA) information. To optimize the performance, hybrid data fusion and tracking algorithms can combine both types of sources and further exploit the mobility of the user. Simulation results for different filter types show the ability of this approach to compensate the lack of satellites by additional TDOA measurements from a future 3GPP-LTE communications system. This paper analyzes the performance in a fairly realistic manner by taking into account ray-tracing simulations to generate a coherent environment for GNSS and 3GPP-LTE.